Green synthesis of paspalum scrobiculatum mediated copper oxide nanoparticles and its anti-bactericidal activities - Agila, Aranganathan; Jeyaleela, Dayana; Bharathy, Stella; Vimala, Rosaline; Sheela, Margrat; Vimala, Sivasangu; Gayathri, Kasirajan (Asia-Pacific Journal of Science and Technology, 2023)
This research mainly aimed to explore the sustainable green biosynthesis of copper oxide nanoparticles (CuONPs) derived from ethanolic extract of Paspalum scrobiculatum. P. scrobiculatum mediated copper oxide nanoparticles (PS-CuONPs) were synthesized by a simple, low-cost, and effective precipitation method. Qualitative screening tests on ethanolic extract of P. scrobiculatum reveal the flavonoids, phenols, terpenoids, proteins, and carbohydrates present in it. The green synthesized CuONPs were characterized by various techniques such as UV, Fourier Transform-Infrared (FT-IR), X-Ray Diffraction (XRD) analysis, Scanning Electron Microscope (SEM), and Energy Dispersive X-Ray Analysis (EDAX) to confirm their existence. The size and morphology of the synthesized PS-CuONPs were observed by XRD and SEM analysis respectively which found that the average size is to be 43.96 nm and has a rectangular shape. The EDAX of PS-CuONPs showed the existence of copper (Cu) and oxygen elements (O) in 53.46% and 46.44% respectively. The anti-bactericidal activity of synthesized PS-CuONPs against five bacterial strains was studied by the disc diffusion method. PS-CuONPs showed noticeable inhibitory action against the pathogen Pseudomonas aeruginosa (5.0±0.30 mm) and on Proteus vulgaris it profound no inhibitory effect. Thus, the synthesized PS-CuONPs played a vital role in bactericidal activity which can be an alternative antibacterial agent against infection-causing above pathogens.